“Speeches” of Sigismund II’s Courier, Mikhail Garaburda, Addressed to the Crimean Qalga Muhammad Giray (1559) - A.A. Gorsky (Золотоордынское обозрение, 2017)
The author of the article for the first time publishes completely the “speeches” of Mikhail Garaburda – the courier of the Polish king and the Great Lithuanian prince Sigismund II – addressed to Qalga of the Crimean Khanate Muhammad Giray, which were intercepted in 1559 by the voivode D.Adashev and presented by Ivan the Terrible to the Lithuanian side in 1562. Both the embassy of Mikhail Garaburda in the Crimea and the Dnieper-Crimean campaign of D.Adashev took place in 1559. The Ambassadorial book of the Grand Duchy of Lithuania speaks about Sigismund’s charter and the “speeches” of his courier. It is noteworthy that Sigismund’s charter and M.Garaburda’s “speeches” were used by the Russian side only in the course of the negotiations in 1562, that is, three years after they had been delivered to Moscow.